2000
DOI: 10.1002/14651858.cd002215
|View full text |Cite
|
Sign up to set email alerts
|

Capitation, salary, fee-for-service and mixed systems of payment: effects on the behaviour of primary care physicians

Abstract: Indicates the major publication for the study 11 Capitation, salary, fee-for-service and mixed systems of payment: effects on the behaviour of primary care physicians (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
254
4
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(273 citation statements)
references
References 26 publications
9
254
4
6
Order By: Relevance
“…A review examined studies from high-income countries and reported that a fee-for-service approach resulted in greater compliance with recommended well-child visits than did capitation payments. 58 Additionally, moderate-quality evidence shows that defaulter tracking-reminder and recall strategies in particular-eff ectively increases routine childhood immuni sation rates in high-income countries. 59,60 Improving quality of care…”
Section: Improving Continuity Of Carementioning
confidence: 99%
“…A review examined studies from high-income countries and reported that a fee-for-service approach resulted in greater compliance with recommended well-child visits than did capitation payments. 58 Additionally, moderate-quality evidence shows that defaulter tracking-reminder and recall strategies in particular-eff ectively increases routine childhood immuni sation rates in high-income countries. 59,60 Improving quality of care…”
Section: Improving Continuity Of Carementioning
confidence: 99%
“…Seminal articles have presented theoretical models of GP behaviour (Ellis & McGuire, 1986;Harsanyi, 1955;McCombs, 1984;McGuire, 2000;Thornton & Eakin, 1997) and a substantial amount of empirical research has been conducted on the impact of organizational characteristics on delivery of GP services, focusing mostly on remuneration systems (Ellis & McGuire, 1990;Gosden et al, 2000;Laffont & Tirole, 1993) and the GP gate keeper role (Brekke et al, 2007;Dusheiko et al, 2006). However, much less is known about doctors' behaviour in publicly-oriented systems which have a high degree of focus on costcontainment and guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Under this interpretation, the coefficient on effort should be the value placed on cure by the patient. 18 This • Both v rich and v poor are indifferent between the two doctors. This follows since they are kept at their reservation utility by both doctors; all differences in the quality provided are fully captured by changes in the price charged.…”
Section: Simple Behavioral Models With Alternative Market Closure Rulesmentioning
confidence: 96%